(untitled) (Ameghiniana, 2013)
The Ordovician Suri Formation in NW Sierra de Narváez (Famatina System) represents in part a volcanicIastic shelf related to a volcanic arc. Fossil concentrations are locally abundant within the shelf sequence. Different types and subtypes are defined according to genetic processes: sedimenlologic concentrations (subtypes ST and SV), mixed biogenic-sedimentologic concentrations (subtypes MSC and MBR) and diagenetic concentrations (subtype DC). Subtype ST was formed by storm action and is present throughout the sequence. Two variaties, proximal and distal, are distinguished. Subtype SV is related to voJcanicIastic debris f1ows. It characterizes the middle shelf environment and is locally present in the inner shelf. Subtypes MSC and MBR represent the sequential interaction of sedimentologic and biogenic processes. The former represents sedimentologic concentrations colonized by bottom dwelling organisms (Orthambonites mollesensis) . The later represents biogenic concentrations reworked by physical processes, but shows evidence of the original community. Both subtypes are present in middle and inner shelf deposits, MBR concentrations being particularly abundant in the inner shelf. Subtype DC was formed by compaction of the surrounding mudstones in the outer shelf. Distribution of fossil concentrations from the analysed volcaniclastic sequence ref1ects different offshore-onshore Irends from those predicted for normal siliciclastic shelves. Sedimenlological processes are dominant throughout the shelf, inhibiting typical environmental gradients as evidenced by fossil concentrations. It is suggested that in such active margin basins. Volcanic related processes play a major role affecting the development of the biota.